Surprise the world : the five habits of highly missional people - Frost, Michael, 1961- (Colorado Springs, CO : NavPress, a NavPress resource published in alliance with Tyndale House Publishers, Inc., 2016)
Christianity is a surprising religion. It has changed the world in remarkable ways throughout history simply through Christians living out their faith. More recently, we've become afraid of a habituated Christianity, thinking that routines will rob our faith of its vitality. The net effect is that we've replaced the habits that surprise the world with habits that mimic the world - and both we and the world suffer for it. Integrating the five habits in the BELLS model - Bless others, Eat together, Listen to the Spirit, Learn Christ, and understand yourself as Sent by God into others' lives - will help you spread the gospel organically, graciously, and surprisingly. Michael Frost, a world-renowned expert on evangelism and discipleship, makes evangelism a lifestyle that is fulfilling, exciting, effective, and easy to live out!
Living "questionable" lives -- A new set of habits -- Bless: the first habit -- Eat: the second habit -- Listen: the third habit -- Learn: the fourth habit -- Sent: the fifth habit -- Discipleship, nurture, and accountability.
Includes bibliographical references (pages 121-124)
Keywords: Missions; Evangelistic work; Witness bearing (Christianity)